PELATIHAN TEKNIK PENULISAN ARTIKEL ILMIAH BAGI MAHASISWA DI KOTA PEKANBARU - Naskah Naskah; Wardani Purnama Sari; Rohani Rohani; Mahdar Ernita; Arif Yasthophi (XXXXX, 2023)
This study aims to determine the importance of publishing scientific papers for students. The background of this research is students who are not familiar with writing scientific articles. This service activity was carried out offline for 1 day by resource persons using the E-Module. The target group in this service activity is especially Economics and General Education Students from Universities in Pekanbaru with a total of 60 participants consisting of students from various Study Programs. The implementation of this training was carried out by a team of Lecturers of the Economic Education Study Program at the Faculty of Tarbiyah and Teacher Training, namely Ibuk Wardani Purnama Sari, M.Pd. E, Mrs. DR. Rohani, M.Pd, Mr. Manuscript, M.Pd. E, and Mrs. Mahdar Ernita, M.Ed. The resource persons in this training were Mr. Dr. Dicki Hartanto, MM and Mr. Arif Yasthopy, M.Sc. The method used in this service activity is presentation and practice as well as demonstrations. Based on the results of the community service activities, the scientific writing training ran smoothly, the material provided was understandable to the participants so that they could practice directly with examples of theses which were used as journal articles.